Сравнительный анализ результатов исследования отношения населения Украины, Венгрии, Чехии и Польши к рыночным основам экономики - Буслаева, Е. (Социология: теория, методы, маркетинг, 2000)
According to the data gained due to four international sociological researches of 1999 (Ukraine, Poland, Hungary, Czech Republic), the author presents a comparative analysis related to orientations of corresponding populations to certain aspects of economic development in these countries. In particular, there was discussed the attitude of people living in Ukraine and the three other countries towards market relations development and society development distribution regulations.